Metal–Organic Framework/GO Electrocatalysis for Water Splitting: Oxygen Evolution Reaction and Hydrogen Evolution Reaction: A Comprehensive Review - Tariq , Areeba; Ijaz, Areeba; Ali , Fahad; Saeed, Muhammad Talha; Khalid , Samina; Maneeb Ur Rehman; Khan, Muhammad Irshad; Wadood, Abbas; Saif, Sumaira; Munir, Rabia (Indus Journal of Bioscience Research, 2025)
An intriguing concept for creating cutting-edge sustainable energy solutions is the de novo engineering of reticular metal-organic frameworks on top of graphene-based materials. Graphene and its derivatives function as metal-organic framework structuring agents, giving them intriguing morphological, textural, topographical, geographical, interfacial, chemical, electrical, and mechanical properties, thanks to their multifunctional lattice and flat yet flexible sheet structure. The metal-organic framework/graphene-based hybrids’ synergistic advantages made them competitive substitutes for costly noble metal-based catalysts. Despite developments, metal-organic framework/graphene-based nanocatalysts for hydrogen evolution processes were not the main focus of any of the earlier reviews. As providing an overview of the development of hybrid nanocatalysts for hydrogen production, this review seeks to close this knowledge gap. It demonstrates how metal-organic framework catalysts are superior to traditional materials for producing hydrogen and explains why hybridizing pure metal-organic frameworks with graphene and its derivatives broadens the spectrum of hydrogen evolution reactions. Additionally, it summarizes the methods of preparation, looks at distinguishing characteristics, and thoroughly assesses the hydrogen evolution reaction and oxygen evolution reaction performance of the metal-organic framework/graphene-based hybrid electrocatalysts that have been published at this point. Lastly, it reveals the present state, current obstacles, and possible future developments of these hybrids based on metal-organic frameworks and graphene.